Biennial review of infertility : volume 3 - Fauser, Bart C.; Carrell, Douglas T.; Racowsky, Catherine; Schlegel, Peter N. (Springer New York, 2013)
In this third volume, the Biennial Review of Infertility brings together the most up-to-date research and clinical information on male and female infertility, emerging assisted reproductive techniques, and controversial issues in reproductive medicine. An impressive panel of contributors presents cutting-edge information in a clear and well-balanced manner. This volume includes hot topics in reproductive medicine including age and its impact on fertility, lifestyle factors and reproductive health, fertility preservation for cancer patients, reproductive tourism, and a discussion of clinical research design. The expanded section on controversies allows for point/counterpoint discussion between experts with differing opinions on topics like safety of the ICSI procedure and the role of IUI in modern reproductive medicine. Created to provide an ongoing appraisal of current knowledge, the Biennial Review of Infertility stimulates communication amongst all those working to help couples resolve their infertility.